Species Composition and Stand Structure of Puspa (Schima wallichii (DC.) Korth.) in Mount Halimun Salak National Park, Sukabumi - Azkiya, Dhany Nukhaizal; Prijanto Pamoengkas; Bayu Winata (Department of Forest Resources Conservation and Ecotourism - IPB University, 2025)
Puspa is a type of vegetation that can be used to restore forests, and grows in M Halimun Salak National Park. This study aims to analyze the species composition, stand structure and biophysical aspects of Schima wallichii (DC.) Korth. The research method used was vegetation analysis with purposive sampling of 5 plots measuring 50 x 50 meters based on the height of the research location. The results showed that puspa dominated the study site with high density at the seedling level and low at the tree level. The horizontal structure of puspa at the study site shows an inverted “J”, indicating that natural succession is well underway. The distribution of puspa in the plot shows a clustered distribution. The temperature and humidity of the study site were relatively uniform, the slope was in the steep and very steep class, while the thickness of litter and residual organic matter was relatively uniform, except in plot 2.